2016
DOI: 10.1021/acs.organomet.6b00209
|View full text |Cite
|
Sign up to set email alerts
|

Double Insertion of Thiophene Rings in Polyynediyl Chains to Stabilize Nanoscaled Molecular Wires with [Cp*(dppe)Fe] Termini

Abstract: International audienceThe dinuclear iron complexes [Cp*(dppe)Fe-C C C4H2S-(C C)(x)-C4H2S-C C-Fe(dppe)Cp*] (2, x = 1; 3 x = 2) and [Cp*(dppe)Fe-C C-C4H2S-C C-C C-Fe(dppe) Cp*] (4) were prepared in one -pot procedures from known organometallic precursors. Compound 2 was obtained from Cp,*(dppe)Fe-C C-C4H2S-C C-C4H2S-C CH (6) and Cp*(dppe)FeCl (5) in 74% yield. Its relative 3, isolated in 84%, resulted from the oxidative coupling of Cp*(dppe)Fe-C C-C4H2S-C CH (7) in the presence of Cu(OAc)(2) and 1,8-diazabicyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 102 publications
0
18
0
Order By: Relevance
“…Within the broad range of bridging ligands examined within [L n M(µ‐bridge)ML n ] + complexes, thiophene derivatives have attracted attention,, with the lower aromaticity of the heterocyclic ring in comparison with benzene thought likely to lead to increased contributions from a cumulene‐like ground state and more extensively delocalised electronic structures , . For example, Lapinte and Lo Sterzo and their respective co‐workers have reported that 2,5‐diethynylthiophene‐linked Fe(dppe)Cp* and Fe(dppe)Cp [Cp = cyclopentadienyl, Cp* = pentamethylpentadienyl, dppe = 1,2‐bis(diphenylphosphino)ethane] termini are more strongly coupled than the 1,4‐diethynylbenzene‐bridged analogues , .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the broad range of bridging ligands examined within [L n M(µ‐bridge)ML n ] + complexes, thiophene derivatives have attracted attention,, with the lower aromaticity of the heterocyclic ring in comparison with benzene thought likely to lead to increased contributions from a cumulene‐like ground state and more extensively delocalised electronic structures , . For example, Lapinte and Lo Sterzo and their respective co‐workers have reported that 2,5‐diethynylthiophene‐linked Fe(dppe)Cp* and Fe(dppe)Cp [Cp = cyclopentadienyl, Cp* = pentamethylpentadienyl, dppe = 1,2‐bis(diphenylphosphino)ethane] termini are more strongly coupled than the 1,4‐diethynylbenzene‐bridged analogues , .…”
Section: Introductionmentioning
confidence: 99%
“…[48,69] Many other bimetallic complexes and metallopolymers with 2,5-diethynylthiophene-based bridging ligands are also known to offer highly delocalised electronic structures with significant contributions from the bridging ligand to the frontier molecular orbitals. [36,49,65,[75][76][77][78][79][80][81][82][83] Against this backdrop of long-standing interest in the properties of bimetallic complexes featuring (oligo)thiophene-based bridges, there has been increasing interest in genuine mixedvalence compounds featuring oligofuran-based bridging ligands. [84][85][86][87] Gidron and Bendikov reported that oligofurans can offer stronger electronic coupling between ferrocenyl redox units than oligothiophenes.…”
Section: Introductionmentioning
confidence: 99%
“…The atomic contributions computed for the HOMO of the neutral model compound [ 8' ], suggest that in the corresponding mono‐oxidized species the spin density should be equally distributed between the metallic centers, the ethynyl fragments and the aromatic ring. On the other hand, derivative complexes with longer spacers such as [µ‐C≡C–(2,5‐SC 4 H 2 )–(C≡C) X –(2,5‐SC 4 H 2 )–C≡C] ( x = 1, 2) belong to the localized Class‐II MV compounds …”
Section: One Electron Less: Toward Mixed‐valence Complexesmentioning
confidence: 99%
“…Similarly, the use of a thiophene group in the organic bridge leads to the cationic system [8] + showing the electronic properties of a strongly coupled mixed-valence Class-III complex. [111,112] [114] Recently, the monocationic complexes [M(dppe)Cp*] 2 [μ-C≡C-(2,5-SC 4 H 2 )-C≡C + ] (M = Fe, Ru) were investigated both experimentally and theoretically. [115] As expected, calculations have shown that the spin density is evenly distributed over the metal-bridge-metal backbone.…”
Section: Modification Of the Carbon Linker To Tune Electronic Communimentioning
confidence: 99%
“…Thiophene oligomers (and polymers) are widely studied because of their electroconductive and photonic properties. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Application of α-connected, conjugated thiophene units in chain stuctures 1,[5][6][7] and α,β-fused thiophene rings in band structures 1,2,4,[8][9][10][11][12] are finding wide application as organic conductors/superconductors 4,7,8 and non-linear optical materials. 1,5,6,9 In addition, oligothiophenes are appealing units to act as spacer-ligands between metal fragments for potential long distance metal-metal communication.…”
Section: Introductionmentioning
confidence: 99%